The Effect of Superstition on Health: Evidence from the Taiwanese Ghost Month - Martin Halla; Chia-Lun Liu; Jin-Tan Liu (Institute of Labor Economics (IZA), 2019)
Superstition is a widespread phenomenon. We empirically examine its impact on health-related behavior and health outcomes. We study the case of the Taiwanese Ghost month. During this period, which is believed to increase the likelihood of bad outcomes, we observe substantial adaptions in health-related behavior. Our identification exploits idiosyncratic variation in the timing of the Ghost Month across Gregorian calendar years. Using high-quality administrative data, we document for the period of the Ghost Months reductions in mortality, hospital admissions, and births. While the effect on mortality is a quantum effect, the latter two effects reflect changes in the timing of events. Efficient public health policy should account for emotional and cultural factors.
Keywords: I12; D83; D91; Z12; 330; superstition; false beliefs; health; risky activities; health-care utilization; mortality; fertility; birth outcomes